Identification and genomic characterization of the first isolate of bluetongue virus serotype 5 detected in Australia. Issue 2 (12th February 2019) - White, John R.; Williams, David T.; Wang, Jianning; Chen, Honglei; Melville, Lorna F.; Davis, Steven S.; Weir, Richard P.; Certoma, Andrea; Di Rubbo, Antonio; Harvey, Gemma; Lunt, Ross A.; Eagles, Debbie
Abstract: Bluetongue virus (BTV), transmitted by midges (Culicoides sp), is distributed worldwide and causes disease in ruminants. In particular, BT can be a debilitating disease in sheep causing serious trade and socio‐economic consequences at both local and global levels. Across Australia, a sentinel cattle herd surveillance program monitors the BTV activity. Prior to 2014, BTV‐1, ‐2, ‐3, ‐7, ‐9, ‐15, ‐16, ‐20, ‐21 and ‐23 had been isolated in Australia, but no bluetongue disease has occurred in a commercial Australian flock. We routinely use a combination of serology, virus isolation, RT‐PCR and next generation and conventional nucleotide sequencing technologies to detect and phylogenetically characterize incursions of novel BTV strains into Australia. Screening of Northern Territory virus isolates in 2015 revealed BTV‐5, a serotype new to Australia. We derived the complete genome of this isolate and determined its phylogenetic relationship with exotic BTV‐5 isolates. Gene segments 2, 6, 7 and 10 exhibited a close relationship with the South African prototype isolate RSArrrr/5. This was the first Australian isolation of a Western topotype of segment 10. Serological surveillance data highlighted the antigenic cross‐reactivity between BTV‐5 and BTV‐9. Phylogenetic investigation of segments 2 and 6 of these serotypes confirmed their unconventional relationships within the BTV serogroup. Our results further highlighted a need for a revision of the current serologically based system for BTV strain differentiation and importantly, implied a potential for genome segments of pathogenic Western BTV strains to rapidly enter Southeast Asia. This emphasized a need for continued high‐level surveillance of vectors and viruses at strategic locations in the north of Australia The expansion of routine characterization and classification of BTV to a whole genome approach is recommended, to better monitor the presence and level of establishment of novel Western topotype segments within the Australian episystem. Abstract : We report on the first isolation of bluetongue virus (BTV) serotype 5 in Australia and detail its full genetic characterization and phylogenetic relationships with Eastern and Western BTV topotypes. We also present related serological data and observations that further highlight acknowledged problems with aspects of the current system of BTV serotype classification.